2020
DOI: 10.3390/su12176835
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Decoupling between Urbanization Level and Urbanization Quality in China

Abstract: After the first industrial revolution, urbanization level worldwide has increased rapidly. As the largest developing country in the world, China has witnessed a rapid improvement in its urbanization level in recent years. Nevertheless, the quality of urbanization has not been improved simultaneously. The relationship between the level and the quality of urbanization has thus become a hot topic for researchers. By introducing the concept and model of decoupling in the field of resources and environment into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Taubenbock [74] analyzed the urbanization development trends and patterns of megacities with populations over 10 million from a global scale, Georg [75] identified the corridor space of major cities in the world according to night light data, and Yu [76] analyzed the urbanization process of six major Chinese cities and its impact on the local environment from a multidimensional perspective of land, population, and economy. Zhang evaluated the relationship between the urbanization scale and quality of 285 prefecture-level cities in China for the period of 2005-2014 and concluded that the two showed eight decoupling points [77].…”
Section: Research Scalementioning
confidence: 99%
“…Taubenbock [74] analyzed the urbanization development trends and patterns of megacities with populations over 10 million from a global scale, Georg [75] identified the corridor space of major cities in the world according to night light data, and Yu [76] analyzed the urbanization process of six major Chinese cities and its impact on the local environment from a multidimensional perspective of land, population, and economy. Zhang evaluated the relationship between the urbanization scale and quality of 285 prefecture-level cities in China for the period of 2005-2014 and concluded that the two showed eight decoupling points [77].…”
Section: Research Scalementioning
confidence: 99%
“…Reasonable urbanization can effectively promote the sustainable development of cities [32,33]. Guan et al [9,34] suggested that urbanization is an inevitable requirement for promoting social progress, and traditional land-centered urbanization is typical of "incomplete urbanization" and "low-quality urbanization". Zhang et al [34] introduced the concept of "decoupling" in the environmental field and established a comprehensive index system on urbanization quality, which systematically evaluated the relationship between the level and quality of urbanization.…”
Section: Urbanizationmentioning
confidence: 99%
“…Guan et al [9,34] suggested that urbanization is an inevitable requirement for promoting social progress, and traditional land-centered urbanization is typical of "incomplete urbanization" and "low-quality urbanization". Zhang et al [34] introduced the concept of "decoupling" in the environmental field and established a comprehensive index system on urbanization quality, which systematically evaluated the relationship between the level and quality of urbanization. Shi et al [35] constructed the evaluation index system of urbanization coordination level based on the quality and scale of urbanization; and analyzed relevant spatial correlation, spatial difference, and spatial pattern evolution characteristics.…”
Section: Urbanizationmentioning
confidence: 99%
“…According to the baseline analysis described in Section 3.1, comprehensive urbanization can improve the health conditions of middle-aged and elderly people. However, owing to the multidimensionality [26], spatial variability [43], and imbalance [44] in China's urbanization, there are also significant regional and urban differences in the impact of urbanization on health [45]. Section 3.2 reveals this influence to a greater extent by exploring the heterogeneity of the dual effects of urbanization on health based on the multidimensionality of urbanization, regional differences, and different city types.…”
Section: The Heterogeneity Analysis Of Urbanization On Chronic Diseases In Middle-aged and Elderly Peoplementioning
confidence: 99%